How do you simplify 3( - 3w - 8) + 3( - 8w + 2)?

2 Answers
May 3, 2018

-33w-18

Explanation:

Multiply both parenthesis by 3, by multiplying each component of the parenthesis by 3:

3(-3w-8) = 3*(-3w) + 3*(-8) = -9w-24

3(-8w+2) = 3*(-8w) + 3*2 = -24w+6

And then sum the two results:

(-9w-24)+(-24w+6) =

=-9w-24-24w+6 = -33w-18

May 3, 2018

Answer = -33w-18

Explanation:

Simplify by opening the bracket first for each term.

3(-3w-8) + 3(-8w+2)
(3xx(-3w)) - (3xx8) + (3xx(-8w)) +(3xx2)
(-9w-24)+(-24w+6)
-9w-24-24w+6
-33w-18